Neurobehavioral test performances in lead exposed in lead exposed workers, 1996 - Mazrura Sahani,; Noor Hassim Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Neurobehavioral test has been used extensively and successfully in many countries to determine neurotoxic effects of various compounds. To determine neurotoxic effects of lead, a cross sectional studies was conducted on 141 male workers from two local battery manufacturing factories using' Neurobehavioral Core Test Batteries' ( NCTB) from' World Health Organisation'. These NCTB consist of several tests which can highlight various neuropsychological functions and a list of questionnaire for subjective symptoms. The workers, were divided into two groups based on their blood lead levels ( PbB ), the first group for those with PbB < 40 µg/dl with mean PbB 27.19 ± 10.23 and the second group with PbB > 40 µg/dl with mean PbB 53.10 ± 11.13. Student t-test has shown significant different between the two groups in neurobehavioral test performance such as Digit Symbol ( p= 0.02 ), Digit Backward ( p=0.01 ), Santa Ana preferred hand ( p=0.04 ), Santa Ana both hands ( p=0.02 ), Aiming Pursuit Test ( p=0.0002) and Trail B ( p= 0.0004 ). Workers from the second group also reported higher subjective symptoms of weakness in lower limbs and anorexia. Factors which have influenced on PbB were jobs category ( p=0.0001 ), work duration (p=0.04 ), chemical exposure ( p= 0.04 ), previous lead exposure ( p= 0.01 ) and usage of personal protective device ( p= 0.04 ). Significant correlation was found between PbB and neurobehavioral test performance such as Digit Symbol ( r= -0.04348 ), Digit Forward ( r= -0.2107 ), Digit Backward ( r= - 0.0003 ), Aiming Pursuit Test .( r= -0.2476 ) and Trail B ( r='0.3040 ). Regression analysis has shown reduction in cognitive and concentration functions with PbB level less that 30 µg/dl and maximum lead effect at Digit Symbol's score of 40. This study has shown that lead has led to impairment of cognitive, concentration, memory and motor steadiness functions and has proven the ability of neurobehavioral test in detecting lead toxicity at low levels.